TITLE: UNDERSTANDING THE CONCEPT OF INTERROGATION OF THE SUSPECT AND THE ACCUSED IN CRIMINAL PROCEDURAL LAW (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article describes the procedure for questioning the suspect and the accused, the terms of their interrogation, their rights and obligations, the legal basis for interrogation the suspect and the accused, the presumption of innocence, and the legal protection of the suspect and the accused.